Criminal Law Policy Against the Development of Criminal Acts of Sexual Violence Aims to Create Gender Justice - Irda Nur Khumaeroh; Sri Endah Wahyuningsih (Universitas Islam Sultan Agung, 2020)
The criminal act of sexual violence has not been explicitly regulated in the Criminal Code (KUHP). In its development, Komnas Perempuan and the Service Provider Forum (FPL) initiated and compiled the Bill on the Elimination of Sexual Violence (RUU PKS). This writing formulates 2 (two) things, namely: criminal and problematic legal policies against criminal acts of sexual violence according to the Criminal Code and its development in the PKS Bill which aims to create gender justice.The approach method used by juridical sociology is a legal research method used in an effort to see and analyze a real rule of law that exists in society. Writing specifications use descriptive analysis, sources and types of data used primary and secondary data. Data collection methods by interview, library research, document study, and use qualitative data analysis methods. The theory used in conducting the analysis is the Pancasila theory of justice, the theory of legal certainty, and the theory of neutralization.The criminal law policy regarding criminal acts of sexual violence according to the Criminal Code regulates adultery, rape, intercourse with underage women, and revocation. However, the development of the PKS Bill on sexual violence was formulated into 9 (nine) types. The problem is in the legal system (substance, structure, and legal culture) which has not been in favor of justice for victims.Keywords: Criminal Law Policy, Sexual Violence, Gender Justice